Molecular Characterization Of Trichodermaspp. Isolated From Saline Soil Using Rapd Markers (Journal of Plant Disease Sciences, 2021)
The present study was conducted to characterize the molecular variation in Trichodermaspp isolated from saline tract of Vidarbha region. The RAPD (Random Amplified Polymorphic DNA) procedure withnine primers of OPA series were used to distinguish between Trichoderma spp. Nine RAPD primers of OPA series were produced 61 scorable bands among them 57 bands were polymorphic and level of polymorphism was up to 93.44%. Three primers namely OPA-13, OPA-10 and OPA-20 each showed monomorphic band. Similarity coefficient value ranged from 0.923 to 0.143 across Trichoderma isolates indicating the diversity among isolates. On the basis of dendrogram the isolates were divided into three clusters. Cluster –A, includes TD-1, TT-2, TC-3, TS 4 and TJ-5. Second group is named as cluster –B which includeTM-6. Third group is named as cluster -C which includes TA-7 and TA-8. The TJ-5 was found to have higher similarity index and the TM-6 was found to have lower similarity index. The maximum and minimum value of cophenetic matrix was 0.923 and 0.255 respectively. Isolate TS-4 was found to have a higher Cophenetic distance matrix with TJ-5 (0.923) and TM-6 with all isolates (0.255).
Keywords: Trichoderma; Molecular Characterization; RAPD; Diversity